It is essentially acknowledged that discounted cash flows should always be calculated by management when making long-term investment decisions. Why is this so? - Kwadade-Cudjoe, Francis (Archives of Business Research, 2021)
Investment is sacrifices made now / future in anticipation of upcoming benefits. Long-term investment is the act of using money to acquire items, normally fixed assets, and is a pre-requisite for any modern organization to have them. Organizations are looking for capital to expand their frontiers to capture cheap labour for manufacturing their products, i.e. globalization. The struggle for survival of organizations, therefore hinge precariously on the ability of the enterprise to successfully invest in long-term debts, and managing the resource judiciously to thrive. However, banks and venture capitalists are not ready to contract loans to organizations not competitive. Moreover, the surge of covid-19 pandemic has made the situation dire, as there is no particular haven to fall on. In view of this, discounting the cash flows generated from business activities is perfectly right to accurately account for success of organizations. Non-discounting cash flows generated from business activities is not rigorous to properly account for success of organizations. In addition, the competitive strategy adopted by the organization is vital to enable management achieve its goals and objectives, and subsequently attain competitive advantage. Furthermore, it is paramount for the organization’s competitive advantage so achieved to be sustainable.